Social Organization and Knowledge - Billings, Dorothy K. (The Australian journal of anthropology, 1991)
This paper explores the relationship between different types of social organization, on the one hand, and different modes of knowing and types of knowledge, on the other. Some characteristic distinctions are suggested and supported with evidence, both from diverse areas of theory, and from the study of two contrasting Melanesian cultures: that of the Lavongai of New Hanover and the Tikana of New Ireland.